(untitled) - Brigham, Eugene F. (New York, 1986)
Concise, with strong pedagogical features, offers an appropriate mix of intuitive explanations, numerical examples, and real-world applications in a concise and lucid format. Comprehensive and thorough, Concise provides an outstanding coverage of bond valuation and interest rates.
Keywords: Financial management,Management accounting